Internet Use Among Older Adults: Association With Health Needs, Psychological Capital, and Social Capital - Choi, Namkee G; DiNitto, Diana M (JMIR Publications, 2013)
BackgroundPrevious studies have identified socioeconomic status and health status as predictors of older adults' computer and Internet use, but researchers have not examined the relationships between older adults' health needs and psychological capital (emotional well-being and self-efficacy) and social capital (social integration/ties and support networks) to different types of Internet use. ObjectiveThis study examined (1) whether older adults' health conditions and psychological and social capital differentiate Internet users from nonusers, and (2) whether the Internet users differed in their types of Internet use on the basis of their health conditions and psychological and social capital. MethodsData for this study came from the National Health and Aging Trends Study, which is based on a nationally representative sample of US Medicare beneficiaries aged 65 years and older. The sample for this study were those who resided in the community in their own or others' homes (N=6680). Binary logistic regression analysis was used to compare health needs, psychological capital, and social capital among (1) any type of Internet users and nonusers, (2) Internet users who engaged in health-related tasks and Internet users who did not, (3) Internet users who engaged in shopping/banking tasks and Internet users who did not, and (4) Internet users only used the Internet for email/texting and all other Internet users. ResultsDepressive and anxiety symptoms, measures of psychological capital, were negatively associated with Internet use among older adults (odds ratio [OR] 0.83, 95% CI 0.70-0.98, P=.03 and OR 0.79, 95% CI 0.65-0.97, P=.03, respectively), whereas most measures of social capital were positively associated with Internet use. Having more chronic medical conditions and engaging in formal volunteering increased the odds of Internet use for health-related tasks by 1.15 (95% CI 1.08-1.23, P<.001) and 1.28 (95% CI 1.05-1.57, P=.02), respectively, but anxiety symptoms decreased the odds (OR 0.74, 95% CI 0.55-0.99, P=.05). Religious service attendance was negatively associated with Internet use for shopping/banking activities (OR 0.75, 95% CI 0.62-0.91, P=.01). Anxiety symptoms increased the odds of using the Internet only for emails/texting (OR 1.75, 95% CI 1.12-2.75, P=.02), but formal volunteering decreased the odds (OR 0.63, 95% CI 0.43-0.92, P=.02). Other correlates of Internet use solely for emails/texting were older age (80-84 years and ≥85 years), a black or "other" racial/ethnic background, a high school education or less than high school, and lower income. ConclusionsThe findings point to the importance of social capital in facilitating older adults' learning and adoption of Internet technology. Older adults who used the Internet for email/texting purposes only were the most socially and economically disadvantaged group of Internet users. Computer/Internet training for older adults and computer/Internet use for various purposes need to consider the significant role their social capital can play.